If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-12h) + 39 = (-4h) + -17 Reorder the terms: 39 + (-12h) = (-4h) + -17 Reorder the terms: 39 + (-12h) = -17 + (-4h) Solving 39 + (-12h) = -17 + (-4h) Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '(4h)' to each side of the equation. 39 + (-12h) + (4h) = -17 + (-4h) + (4h) Combine like terms: (-12h) + (4h) = -8h 39 + -8h = -17 + (-4h) + (4h) Combine like terms: (-4h) + (4h) = 0 39 + -8h = -17 + 0 39 + -8h = -17 Add '-39' to each side of the equation. 39 + -39 + -8h = -17 + -39 Combine like terms: 39 + -39 = 0 0 + -8h = -17 + -39 -8h = -17 + -39 Combine like terms: -17 + -39 = -56 -8h = -56 Divide each side by '-8'. h = 7 Simplifying h = 7
| x+10=-20 | | 11x+3+6x+12+14=180 | | 8p+12=12+8p | | 73+x-22=283 | | 3(x-4)+5x= | | 176=10x-4 | | -2x+4+3x=-2+11 | | 25+w=175 | | 6n^2+7n=5 | | 8x-2(5x+6)=20 | | x+10x+3x=120 | | -5w+12w+9=4w+42 | | -120+8x=-2x+200 | | .2x=100 | | f(x)=-x+14 | | -2+d=42 | | 24-3r=3 | | 8x-6+2x=24 | | -76+-25t=674 | | 5(n+3)+5=-24 | | x^2-6x=8x+x^2 | | 31=2n+9 | | -8x-27=48-5x | | 7d+5-4d= | | 11x-5=7-x | | -6-13=9x+17-8x | | x-45=-31 | | (7-x)18*0.5=144 | | x^2+15x+54=12 | | -9n+-6n-9n-7n+-7n+-6n= | | 11x+16=5y-11 | | -1.5+6= |